Prevalence of internet addiction and its consequences among MBBS students of MP Shah Medical College, Jamnagar, Gujarat - Swati Misra; Pradeep Pithadia; Dipesh Parmar; Naresh Makwana; Sumit Unadkat (Healthline, 2020)
Introduction: Internet is one of the most essential elements in everyday life of everyone. Simultaneously, it’s an emerging public health issue also, especially in our country. Excessive and undisciplined use of internet may lead to many physical, social, psychological and behavioral disorders. Medical students have not only lengthy syllabus but also hefty study hours and internet addiction may affect their scholastic pattern and learning. Therefore, this study was designed to assess prevalence and pattern of internet addiction and its consequences among them. Aims and Objectives: The aim of this cross-sectional study is to determine prevalence and pattern of internet addiction and its ill-effects among medical students of M P Shah Government Medical College, Jamnagar. Methodology: We included all medical students (n=600) of all semesters of MP Shah Medical College and collected data using Dr. Kimberly Young’s Internet addiction scale from October 2019 to December 2019. Informed Consent was taken. Results: We observed that majority of students (82.67%) were average online users. The mean score of internet usage for male and female medical students was 44.22 and 38.48 respectively. Sleep disturbance, impulsiveness, anxiety, emotional liability, lack of interest in study were some of the major consequences of internet addiction among students observed in our study. The study also observed that students tried several methods like Yoga, meditation etc. to get rid of the internet addiction and concentrate on studies. Conclusion: Periodic screening of students should be carried out to identify internet addicts and a comprehensive program or strategies should be formed at institutional level for support and counselling of such students and to avert and cope up with ill effects of internet addiction.